2002
DOI: 10.1124/jpet.302.1.180
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Intervention in Mice Deficient for Succinate Semialdehyde Dehydrogenase (γ-Hydroxybutyric Aciduria)

Abstract: Therapeutic intervention for human succinic semialdehyde dehydrogenase (SSADH) deficiency (␥-hydroxybutyric aciduria) has been limited to vigabatrin (VGB). Pharmacologically, VGB should be highly effective due to 4-aminobutyrate-transaminase (GABA-transaminase) inhibition, lowering succinic semialdehyde and, thereby, ␥-hydroxybutyric acid (GHB) levels. Unfortunately, clinical efficacy has been limited. Because GHB possesses a number of potential receptor interactions, we addressed the hypothesis that antagonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 38 publications
1
88
0
3
Order By: Relevance
“…It may also serve a neuroprotective function, preventing glutamate-induced neuronal excitotoxicity (Chen et al 2001). Taurine has shown benefit in the SSADH-deficient mouse model (Gupta et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It may also serve a neuroprotective function, preventing glutamate-induced neuronal excitotoxicity (Chen et al 2001). Taurine has shown benefit in the SSADH-deficient mouse model (Gupta et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Taurine appears effective in the mouse model of SSADH deficiency when administered from birth (Gupta et al 2002). Early therapy may be the key -a "critical period" during which taurine or other interventions might be beneficial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aldh5a1 −/− mice exhibit developmental delay, ataxia and a seizure disorder that progresses from absence seizures (~post-natal day, P, 15) to lethal status epilepticus (~P25) (Cortez et al, 2004). A variety of pharmacological treatments were attempted to rescue Aldh5a1 −/− mice with limited success (Hogema et al, 2001;Gupta et al, 2002;Cortez et al, 2004). However, it has been reported that pups that continue to suckle beyond weaning age (~P20) live longer than their weanling counterparts, suggesting that the high fat dam's milk may have beneficial effects in this disorder (Hogema et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Gamma-hydroxybutyric acid receptor antagonists have been shown to lead to significant lifespan extension in SSD-deficient mice (Gupta et al 2002).…”
Section: Alternative Therapies/experimental Trials S 32 Succinic Semmentioning
confidence: 99%